The treatment of pain in bone metastasis of cancer with the analgesic decoction of cancer and the acupoint therapeutic apparatus - Guo, R; Zhang, L; Gong, Y; Zhang, B (Journal of traditional Chinese medicine, 1995)
The pain in 286 cases of bone metastasis of cancer was treated with an analgesic decoction of herbal drugs in combination with the Acupoint Therapeutic Apparatus that generated low frequency electric impulses into the acupoints. This series of patients comprised 104 cases of medium pain and 182 cases of severe pain, which was practically or completely relieved in 17 or 29 minutes respectively after the treatment; the total effective rate was 74.2% for 212 cases, and the duration of analgesic effect lasted 2.7 hours to 5.2 hours, averaging 3.6 hours. The cases that needed considerable dosages of analgesic tablets or sedatives markedly reduced their requests of such drugs. Determination of bone marrow stem cells indicated that the herbal treatment produced effects of promoting and protecting the stem cells. The rate of lymphocyte transformation was 45-76% before the treatment and rose to 57-96% after the treatment, demonstrating an increase of 15.2%, which was statistically significant (P < 0.001). The analgesic effect of the decoction was not correlated to the age and sex of the patients or the variety of cancer, except that it was not effective for uterine carcinoma. The main side effects included nausea, vomiting, somnolence, and numbness of the tongue.